Validating the Cambridge Protocol: Reliability of Hip Muscle Strength Measurements Using a Motorized Dynamometer and Electromyography. (September 2022) - Memarzadeh, Arman; Morrison, Andrew Paul; Merzbach, Viviane; Ferrandino, Michael; Arora, Arvind; Claydon-Mueller, Leica S.; Khanduja, Vikas
Background: Muscle weakness is common after injury in athletes and in the presence of hip pathology. It will cause abnormal hip biomechanics and can predict future injury. However, objective measurement of hip muscle strength is difficult to perform accurately and reliably. Therefore, it is challenging to determine when an athlete has returned to preinjury levels of strength. In addition, there is currently no standardized method of obtaining measurements, which prevents the data being compared or shared between research centers. Purpose: The purpose of this study is to comprehensively assess the inter- and intraobserver reliability of our standardized muscle strength measurement protocol. Study Design: Descriptive laboratory study. Level of Evidence: Level 3, inception cohort study. Methods: A total of 16 healthy male volunteers (age = 28.3 ± 7.9 years) were recruited. Those with a previous history of hip injuries or disorders were excluded. These volunteers underwent strength testing according to the Cambridge Protocol on 4 separate occasions, performed by 2 independent assessors. Maximal voluntary contractions, fatigue torque fluctuations, and electromyography measurements were recorded. Intra- and interobserver reliability was assessed using intraclass correlation coefficient (ICC). Results: Good-to-excellent correlation was seen for both intra- and interobserver reliability across almost all hip movements for maximal contractions: ICC ranged 0.78 to 0.93 and 0.78 to 0.96, respectively. The standard error of the mean for all hip movements was also extremely low at 2% to 3%. Conclusion: The Cambridge Protocol is a highly reliable method for objective measurement of hip muscle strength. We recommend future studies use this protocol, or the principles underpinning it, to enable data sharing and comparison across different studies. Clinical Relevance: This is a description and analysis of hip muscle strength measurement. If widely used, it will allow for accurate and objective strength assessment and closer monitoring of hip injuries and pathology.